Solve Algebraically by Factoring. Solve for x. (x – 3)(x – 2) = 0

Question

Solve Algebraically by Factoring.
Solve for x.
(x – 3)(x – 2) = 0

in progress 0
Amelia 2 hours 2021-09-12T13:34:29+00:00 2 Answers 0

Answers ( )

    0
    2021-09-12T13:35:36+00:00

    X1=2 x2=3 hope this helps

    0
    2021-09-12T13:36:09+00:00

    Answer:

    3,2

    Step-by-step explanation:

    (x – 3)(x – 2) = 0

    x – 3 = 0 or x – 2 = 0

    x = 3 or x = 2

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )